Application of CAPS markers for diversity assessment in grass pea (Lathyrus sativus L.) - Shiferaw, Eleni; Porceddu, Enrico; Pé, Enrico; Ponnaiah, Maharajah (Biodiversity: Research and Conservation, 2017)
Genetic diversity among 20 Lathyrus sativus L. accessions from Ethiopia was investigated by using Cleaved Amplified Polymorphic Sequence (CAPS) markers. Genetic diversity statistics showed presence of a moderate level of genetic variation in the analysed accessions (P = 69.77%, Hs = 0.278). Analysis of genetic differentiation showed existence of a low level of differentiation between accessions, which accounted for only 7% of the total variation and most of the variation was due to differences among individuals within accessions (93%). Both cluster and principal coordinate analyses revealed minimal grouping of accessions based on geographical origin implying that local varieties of grass pea with different genetic backgrounds were distributed among various administrative regions in Ethiopia. The CAPS markers employed in our study demonstrated the utility of such markers for genetic diversity assessment in grass pea.